POETIC DREAM MYTHOLOGY IN M. YU. LERMONTOV’S WORKS - L. A. Khodanen; Yamadzy Asuta (Вестник Кемеровского государственного университета, 2015)
The addresses the poetics of the dream motifs in M. Yu. Lermontov’s works. In Lermontov’s earlier works the lyrical situations and dream symbolics were being developed. Their foundation was the Christian anthropology, which was reflected in the “night cycle” and in the range of poems, which included prophesy. In the 1837 – 1841 poems new forms of hero’s dream state appear, including visions about the past, prophesy about his own fate, which are presented as complete and visible pictures. The author’s myth is developed, in which the hero is able to overcome the Earth’s time and to unite his existence with nature and universe rhythms.